Oxygen-carrying nanoparticle-based chemo-sonodynamic therapy for tumor suppression and autoimmunity activation. (28th April 2021) - Zhang, Yanan; Qiu, Na; Zhang, Yu; Yan, Huixian; Ji, Jianbo; Xi, Yanwei; Yang, Xiaoye; Zhao, Xiaogang; Zhai, Guangxi
Abstract : DTX/CS–Rh–PFC nanoparticles are hydrolyzed by glutathione in tumor cells, releasing DTX and oxygen molecules, and thus exhibit good anti-tumor ability. Abstract : Sonodynamic therapy (SDT) is a promising non-invasive approach for cancer therapy. However, tumor hypoxia, a pathological characteristic of most solid tumor types, poses a major challenge in the application of SDT. In this study, a novel CD44 receptor-targeted and redox/ultrasound-responsive oxygen-carrying nanoplatform was constructed using chondroitin sulfate (CS), reactive oxygen species (ROS)-generating sonosensitizer Rhein (Rh), and perfluorocarbon (PFC). Perfluoroalkyl groups introduced into the structures preserved the oxygen carrying ability of PFC, increasing the oxygen content in B16F10 melanoma cells and enhancing the efficiency of SDT. Controlled nanoparticles without PFC generated lower ROS levels and exerted inferior tumor inhibition effects, both in vitro and in vivo, under ultrasound-treatment. In addition, SDT promoted immunogenic cell death (ICD) by inducing exposure of calreticulin (CRT) after treatment with CS–Rh–PFC nanoparticles (NPs). The immune system was significantly activated by docetaxel (DTX)-loaded NPs after SDT treatment due to the enhanced secretion of IFN-γ, TNF-α, IL-2 and IL-6 cytokines and tumor-infiltrating CD4+ and CD8+ T cell contents. Our findings support the utility of CS–Rh–PFC as an effective anti-tumor nanoplatform that promotes general immunity and accommodates multiple hydrophobic drugs to enhance the beneficial effects of chemo-SDT therapy.